2006
DOI: 10.1111/j.1600-0528.2006.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different diagnostic thresholds on dental caries calibration – a 12 month evaluation

Abstract: It was possible to use the methodology proposed in this study in epidemiological surveys when examining the mixed dentition, although new strategies to improve training in IL diagnosis and calibration are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 21 publications
2
61
0
11
Order By: Relevance
“…[3][4][5][6][7] The subjects were examined on the same day, first by clinical and radiographic examination by one examiner, using an 8-inch round cone that was placed in contact with the ring of the film-holding system (RINN XCP; Dentsply, York, UK) placed in contact with the patient cheek during exposure. Then, the second examiner (blinded from the previous) performed the transillumination assessment placing the mouthpiece over the occlusal surfaces.…”
Section: Sample and Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] The subjects were examined on the same day, first by clinical and radiographic examination by one examiner, using an 8-inch round cone that was placed in contact with the ring of the film-holding system (RINN XCP; Dentsply, York, UK) placed in contact with the patient cheek during exposure. Then, the second examiner (blinded from the previous) performed the transillumination assessment placing the mouthpiece over the occlusal surfaces.…”
Section: Sample and Detection Methodsmentioning
confidence: 99%
“…Clinically, the International Caries Detection and Assessment System (ICDAS) is a visual scoring system to assess caries lesions at both initial and manifest thresholds. [3][4][5][6][7] Radiographic examination is highly sensitive for detecting caries on surfaces that cannot be inspected visually, such as approximal surfaces. However, limitations in revealing the early stages of the disease have been reported, 8 and the risk associated with radiographic exposure needs to be taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…In these populations, non-cavitated caries lesions show a slow progression pattern and are observed principally in early stages. 9,10 Caries epidemiology also involves the study of variables that can influence its occurrence and severity, including social, demographic, and behavioral factors, such as ethnicity, family income, parents' educational level, knowledge and beliefs of them and oral hygiene habits. Cross-sectional studies have shown the complex interaction among these factors and caries in preschoolers.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, the choice of a criterion of caries detection that includes non-cavitated lesions and detect early injuries could increase sensitivity, mainly in populations with low prevalence of the disease, in which carious lesions have a low progression rate and are commonly found in the initial stages (6).…”
Section: Introdutionmentioning
confidence: 99%